Binary dislocation junction formation and strength in hexagonal close-packed crystals. (April 2016) - Wu, Chi-Chin; Aubry, Sylvie; Arsenlis, Athanasios; Chung, Peter W.
Abstract: This work examines binary dislocation interactions, junction formation and junction strengths in hexagonal close-packed ( hcp ) crystals. Through a line-tension model and dislocation dynamics (DD) simulations, the interaction and dissociation of different sets of binary junctions are investigated involving one dislocation on the ( 01 1 ¯ 0 ) prismatic plane and a second dislocation on one of the following planes: (0001) basal, ( 1 1 ¯ 00 ) prismatic, ( 1 1 ¯ 01 ) primary pyramidal, or ( 2 ¯ 112 ) secondary pyramidal. Varying pairs of Burgers vectors are chosen from among the common types: the basal type < a > : 1 3 < 11 2 ¯ 0 >, prismatic type < c >:<0001>, and pyramidal type < a + c > : 1 3 < 11 2 ¯ 3 ¯ > . For binary interaction due to dislocation intersection, both the analytical results and DD-simulations indicate a relationship between symmetry of interaction maps and the relative magnitude of the Burgers vectors that constitute the junction. Using analytical formulae, a simple regressive model is also developed to represent the junction yield surface. The equation is treated as a degenerated super elliptical equation to quantify the aspect ratio and tilting angle. The results provide analytical insights on binary dislocation interactions that may occur in general hcp metals. Highlights: The binary dislocation interactions are examined for seven hcp crystals. The size, shape, and symmetry of binary dislocation interaction maps depend on the Burgers vectors. All junction yield surfaces of tested configurations across different crystals have similar shapes. DD simulations with and without dislocation interactions predict similar junction strengths. An empirical polynomial equation is developed for the junction yield surface plots based on the line tension model.